Gambaran Sifat Organoleptik dan Daya Terima Bakso Ikan dengan Penambahan Daun Kelor (Clarimori) pada Anak Sekolah Dasar - Yunita, Asry; Darawati, Dr. Made; Suranadi, Luh; Widiada, I Gde Narda (Poltekkes Kemenkes Mataram, 2023)
Background : Fish balls are one of the foods that are very popular and favored by the people of Indonesia. Fish balls are usually made from a mixture of fish meat or surimi, tapioca flour as a filler and seasoning – seasoning. ResearchMethod : This study uses experimental methods in the laboratory with a complete randomized design (RAL). Test organoleptic properties using the hedonic test method. The acceptability test was conducted with a target of 30 elementary school children aged 8-12 years. Result: The results of organoleptic studies of fish ball products are known that the best treatment level is t3 (addition of 20% Moringa leaves). The nutritional content of fish balls in 100 grams is energy 134 kcal, protein 18 grams, fat 1.3 grams, and carbohydrates 11 grams. Meanwhile, in 1 serving (75 grams) the nutritional content is 100 kcal of energy, 13 grams of protein, 1 gram of fat, and 9 grams of carbohydrates. The acceptability of clorimori meatballs for school children aged 8 – 12 years is 23 children in the category of good acceptability. Conclusion : The addition of Moringa leaves with the best results is in t3 treatment (20%). In 1 serving (75 grams) with nutritional content of 100 kcal energy, 13 grams of protein, 1 gram of fat, and 9 grams of carbohydrates. The acceptability of fish balls given to 30 elementary school children in the MarongJamaq Utara neighborhood showed good acceptance of 76.7% and less acceptability of 23.3% of people.